Understanding Learning and Students from the Quranic Perspective - Siregar, Maralottung; Rini, Khatami Ayu; Saputri, Sela; Hanum, Sri Junaida (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
Knowledge is essential for humans to achieve happiness in both worldly life and the hereafter. Acquiring knowledge requires studying and understanding Qur’anic verses related to learning activities. This study employs a thematic interpretation (tafsir tematik) method. The findings show that the primary purpose of learning is cultivating awareness, which motivates students to be grateful and devoted to Allah. Tawhid (the oneness of Allah) serves as the fundamental foundation of all learning activities. Furthermore, teachers should regard students not merely as objects but as active participants in education; a creative teacher fosters students’ active engagement. Students’ attitudes toward teachers should reflect noble character (akhlaq al-karimah), emulating the exemplary interactions of the Companions with Prophet Muhammad (peace be upon him).